Human Resource Management Strategies in Enhancing Creativity and Content Production Consistency at NS BOR Channel - Nada Bintang Faradhiba; Agusdin Agusdin (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
The rapid development of the digital creative industry requires effective human resource management to support creativity and content production consistency. NS BOR Channel, as a YouTube channel focused on religious education, faces challenges in maintaining a balance between team creativity and content production consistency. This study aims to analyze the human resource management strategies implemented by NS BOR Channel to improve creativity and consistency in content production. The study employed a descriptive qualitative approach using observation, interviews, and documentation techniques. Informants included the founder, production manager, content creator, video editor, graphic designer, social media strategist, and voice-over and audio editing team. Data were analyzed using the Miles and Huberman model, consisting of data reduction, data presentation, and conclusion drawing. The results indicate that human resource management strategies are implemented through clear task distribution, work planning through brainstorming sessions, intensive communication and coordination, and routine evaluation of content production outcomes. These strategies enhance team creativity through idea exchange and collaboration while maintaining production consistency through scheduling and regular evaluation. The challenges identified include limited production time, difficulties in generating new content ideas, and limited production facilities